2021
DOI: 10.1590/2317-1545v43254684
|View full text |Cite
|
Sign up to set email alerts
|

Thousand-seed weight determination in forest species by image analysis

Abstract: Thousand-seed weight (TSW) is used to calculate the sowing density, number of seeds present in a sample, and predict seed size. Our aim was to establish an alternative methodology for thousand-seed weight determination in forest species using image analysis techniques. The traditional methodology was compared with the alternative one, testing them on seeds from 16 forest species. The traditional method was performed by manually counting eight repetitions of 100 seeds, weighing of samples, and computation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
1
2
0
1
Order By: Relevance
“…Singh et al (2020) reported that a simple foreground area was found to be the best predictor and has a greater association with seed weight. A similar type of image-based seed weight prediction using seed architectural traits has been reported in rice (Singh et al, 2020), wheat (Sabanci et al, 2016), and forest species (Felix et al, 2021).…”
Section: Comparison and Identification Of The Best Prediction Model T...supporting
confidence: 62%
See 2 more Smart Citations
“…Singh et al (2020) reported that a simple foreground area was found to be the best predictor and has a greater association with seed weight. A similar type of image-based seed weight prediction using seed architectural traits has been reported in rice (Singh et al, 2020), wheat (Sabanci et al, 2016), and forest species (Felix et al, 2021).…”
Section: Comparison and Identification Of The Best Prediction Model T...supporting
confidence: 62%
“…(2016) used a Logitech c905 webcam camera to acquire still images and accurately predicted wheat seed weight (99.66%) using a simple polynomial regression model. Similarly, Felix et al. (2021) determined the thousand seed weight (TSW) of seeds harvested from 16 different forest tree species using digital image processing through image J software and demonstrated the comparative advantages (60-80% time savings) of image-based phenotyping for counting seed number, weight, and TSW over traditional manual measurement.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quanto ao peso de mil sementes, houve diferença entre os híbridos, com variação de aproximadamente 1,58 gramas entre o híbrido Hyola 401 com maior peso de mil sementes, e o híbrido Hyola 76 de menor peso (Tabela 1). O peso de mil sementes é uma medida utilizada para diferentes finalidades, dentre elas a comparação da qualidade de lotes de sementes em diversas espécies (FELIX et al, 2021).…”
Section: Resultsunclassified